A comparative study of single dose preoperative antibiotic prophylaxis versus five-day conventional postoperative antibiotic therapy in patient undergoing elective surgical procedure - Basant, Rajesh K.; Kumar, Raj; Pandey, Vinod K.; Saxena, Abhishek; Singh, Vikram; Madeshiyaa, Shivam (International Surgery Journal, 2019)
Background: Surgical site infections (SSIs) increase overall mortality and morbidity and increase the length of hospital stay and overall costs. With the fear of developing wound infection after surgery, author used to administer antibiotics for a period of 7-10days even in clean and clean-contaminated cases. This study aimed to fill that lacunae and there by aid the gradual shift away from over reliance on antibiotics in prevention of SSI, so author can prevent rapid development of resistance against antibiotics, prolonged hospital stays, and drug induced complication. Methods: This facility based prospective study was carried out over a period of 1year involving 102 patients between the age group of 20-70years. All the patients in study group were given a single dose of 1gm (150mg/kg) of injection cefotaxime, 30minute before skin incision. All the cases in the control group received injection cefotaxime 1gm (150mg/kg) I.V. BD for five days. Results: Data in the form of age, sex, type of surgery, post-operative fever, severity of pain and swelling at site of incision, duration of post-operative hospital stay, cost of treatment were noted in prescribed format and statistical analysis was done. Conclusions: Single dose antibiotic prophylaxis is sufficient for clean and clean contaminated surgeries because there was no difference found in SSI either using single dose pre-operative antibiotic prophylaxis or using five days conventional post-operative antibiotic therapy with the added advantage of significant reduction in hospital stay and savings in resources.